Review of Epoicocladius Šulc et Zavřel from China (Diptera, Chironomidae) - Yan, Chuncai; Liu, Ting; Cao, Wei; Zhang, Xinghua; Liu, Wenbin (Zootaxa, 2019)
Epoicocladius Šulc et Zavřel from China is reviewed. Epoicocladius wangi Liu et Yan sp. n. is described and illustrated as male imago from China. The generic diagnosis is amended. Key to the known adult males of the genus and species distribution map worldwide are presented.